Vocational Center Conceptual Model for Empowerment Training in the Field of Metal Fabrication - Nurhaji, Soffan; Abizar, Haris; Ikhsanudin (Indonesian Journal of Community Services Cel, 2022)
This research aimed to develop a conceptual model for vocational centers that empower individuals in the field of metal fabrication. The study used a qualitative approach and data was collected through interviews and observations of individuals involved in metal fabrication training. The results showed that the development of a vocational center based on a conceptual model that emphasizes competence and empowerment can lead to improved training and job opportunities for individuals in the field of metal fabrication. The model consisted of several key components, including a focus on hands-on training, the provision of relevant industry-standard equipment, and the integration of soft skills development into the training curriculum. The findings of this study provide valuable insights for the design and implementation of effective vocational training programs in the field of metal fabrication. The proposed model can be used as a reference for policymakers, vocational center managers, and trainers to enhance the quality and impact of training programs.